2011
DOI: 10.1016/j.seizure.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of electrocorticography in tailored temporal lobe surgery

Abstract: The patients who underwent tailored temporal lobe epilepsy surgery guided by ECoG had similar outcome compared with the patients with epilepsy surgery not guided by ECoG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 29 publications
0
45
0
1
Order By: Relevance
“…The present study, continuously and automatically analyzing IEDRs along the entire surgery, confirms this first observation. Hence, intraoperative monitoring of IEDRs appears to be an indirect measure of ATLR success, therefore showing its potential value as another evaluation modality in epilepsy surgery, in addition to more renowned and well-established techniques such as intraoperative electrocorticography [46,47,48,49]. …”
Section: Discussionmentioning
confidence: 99%
“…The present study, continuously and automatically analyzing IEDRs along the entire surgery, confirms this first observation. Hence, intraoperative monitoring of IEDRs appears to be an indirect measure of ATLR success, therefore showing its potential value as another evaluation modality in epilepsy surgery, in addition to more renowned and well-established techniques such as intraoperative electrocorticography [46,47,48,49]. …”
Section: Discussionmentioning
confidence: 99%
“…ECoG is a useful tool to identify the location of the epileptogenic focus, map the extent of the irritative zone (San-juan et al, 2011) and to assess the completeness of resection. Several studies have established that tailoring surgical resection based on intra-operative ECoG findings resulted in better seizure outcomes (Oliveira et al, 2006;Tripathi et al, 2010;Van Gompel et al, 2009).…”
Section: Utility Of Ecogmentioning
confidence: 99%
“…Several studies have established that tailoring surgical resection based on intra-operative ECoG findings resulted in better seizure outcomes (Oliveira et al, 2006;Tripathi et al, 2010;Van Gompel et al, 2009). Residual hippocampal spikes that persist after resection (during surgery for mesial temporal sclerosis) correlate with poor seizure outcome after surgery (San-juan et al, 2011). ECoG is also eminently suitable for use during excision of developmental malformations of brain, and more so for excision of the highly epileptogenic cortical dysplasias (CDs).…”
Section: Utility Of Ecogmentioning
confidence: 99%
“…In addition to long-term intracranial EEG recordings to identify the seizure onset zone, cortical resections are also tailored in the operating room by including areas with abundant epileptic spikes and seizure-like interictal activity (ictiform patterns) recorded with corticography. 2 Intraoperative localization based on interictal EEG activity would be much more cost-effective than chronic recording to capture spontaneous seizures.…”
mentioning
confidence: 99%
“…4,13 The value of recording interictal spikes with electrocorticography as a biomarker to tailor resections has been disputed. 2 van 't Klooster et al confirmed that spikes are not a good biomarker for the epileptogenic zone, and their removal is not correlated with a good seizure outcome. Perhaps it is time to focus on HFOs, which appear to be reliable biomarkers under appropriate recording conditions.…”
mentioning
confidence: 99%